Procedure to detect the penetration of chlorides into carbonated concrete with silver nitrate - Vieira Pontes, Carla; Costa Reus, Giovana; Calvo, Analiet; H. F. Medeiros, Marcelo (Revista ALCONPAT, 2021)
The main objective of this work is to propose a standard procedure that enables the use of the colorimetric method to measure the depth of chloride penetration during inspections of concrete structures exposed to both chlorides and carbonation. To avoid the occurrence of false positive results, solutions of calcium hydroxide (Ca(OH)2) and sodium hydroxide (NaOH) were tested as a pretreatment. The tests were carried out on carbonated only samples, and on carbonate and chloride contaminated samples. The results show that the NaOH solution eliminates the carbonation interference. Therefore, a suitable method was found to introduce depth readings of chloride contamination in concrete field inspections.